Indigenising the Griffith School of Environment Curriculum: Where to From Here? - Howlett, Catherine; Ferreira, Jo-Anne; Seini, Monica; Matthews, Christopher (The Australian Journal of Indigenous Education, 2013)
This article presents a discussion on a study undertaken by academics within the Griffith School of Environment, Brisbane, Australia that sought to explore the potential of an Indigenised curriculum to attract and retain Indigenous students, and thereby facilitate greater participation of Indigenous students in science. The article highlights the need for staff to be both reflective and reflexive about the limitations their particular knowledge systems may impose on Indigenous ways of knowing and knowledge systems. The article also acknowledges the need for professional development opportunities for staff prior to any attempts towards Indigenisation of the curriculum.